Hot topics in cardio-oncology - Mercurio, Valentina (River Publishers series in biotechnology and medical technology forum., 2021)
Over the last years, thanks to growing advances in the field of cancer therapies, a considerable decrease in cancer mortality has been observed. Unfortunately, such therapies have shown a wide spectrum of cardiotoxicities. This book provides the readers with the latest advances and insights in the ever-expanding field of Cardio-Oncology. Specific topics discussed in the book include the potential role of inflammation in Cardio-Oncology and the description of the different manifestations of cardiotoxicities (including vascular toxicity, systemic hypertension, arrhythmias), analyzing the complex relationships between cancer and heart failure, two conditions whose prevalence increases with ageing. Furthermore, the role of biomarkers and imaging in cardio-oncology is discussed.